Reusable multicriteria decision model to evaluate the integrated sustainability impacts of different alternatives of dietary substitutions - Sara M. Pires; João Fiéis de Melo; Hernan Gomez Redondo; Ricardo Assunção; Géraldine Boué; Beatrice Biasini; Elena Cozzi; Olivier Jolliet; Davide Menozzi; Ana C.L. Vieira (PLoS ONE, 2026)
Policies promoting shifts towards sustainable diets must consider the health, environmental, and socioeconomic impacts of changes and the trade-offs among these impacts across options. Comprehensive assessments are challenged by data uncertainties, diverse metrics, and conflicting interests of stakeholders. The aim of this study was to build a reusable multicriteria model to evaluate the integrated impacts of food substitutions. We applied a multicriteria decision analysis (MCDA) approach that combined input from eight multi-disciplinary experts with evidence collected from scientific literature and public databases across four dimensions: health, environment, economics and social implications of food systems. We tested the approach by assessing the impact of substituting beef with equivalent amounts of pulses in the Portuguese and Danish diets in four scenarios. Results demonstrated an overall positive impact of replacing beef with pulses in both populations, with benefits increasing incrementally with greater levels of substitution. This multicriteria model is adaptable to other contexts and populations, thereby assisting in the development of food policies that consider both health and sustainability concerns.